Exploring of Canva in Improving Writing Skills in English Subjects - Retnowati, Dwi; Mulyanto, Rahmat; Purnami, Sri (International Journal of Engineering, Science and Information Technology, 2025)
The advancement of technology and information has brought significant changes in various aspects of life, including education. One of the impacts of globalization is the advancement of technology and information. Globalization cannot be separated from the rapid development of information and communication technology, the primary supporting factor. Appropriate technology can increase student learning motivation, increase interaction between students and teachers, and facilitate access to information. Educators must consider technology in learning. To present engaging and innovative education, teachers are required to follow technological developments. The intention is to use technology to facilitate the learning process. This study aims to describe the implementation of Canva and analyze its impact on improving writing skills in English subjects at SMP PGRI Saptosari. This study uses a qualitative descriptive method. Data was obtained through observation, questionnaire completion, and documentation. Observations were carried out twice. The study's results indicate improved writing skills, particularly in creating procedure texts for English learning. The obtained data concluded that the creativity assessment indicator increased from the previous average of 64.68 to 85.10. The score jumped from the lesser to the excellent category by 20.42 points. The second increase in diction or word choice resulted in an average value increase from 61.31 to 78.4, moving from the less category to the sufficient one. The last is in the organizational text, which was initially 71.81 and increased to 79.40.